Neutron radiation damage of plastic scintillator UPS 923A and a data driven method in the Z h + E'Iiiss search at the LHC - Mthembu, Skhathisomusa Dumani (My University, 2018)
Plastic scintillators, exposed to radiative environments from high energy charged particles traversing through them in the LHC at CERN, undergo radiation damage. This damage is characterized in terms of the transmittance, luminescence and light yield optical properties of the plastic are tested for changes resulting from exposure of these plastic scintillator samples to fast neutrons of varying fluences. The neutron irradiation was carried out at the IBR-2 reactor of the Frank Laboratory for Nuclear Problems at the Joint Institute for Nuclear Research, at fluences of 1.8-1014 , 1.7-1013 and 3.8-1012 neutrons/cm2 , and compared to a control sample. Results show a small change in the transmittance of the higher energy visible spectrum, and a noticeable change in the light yield of the samples as a result of the damage. There is no change observed on the luminescence as a result of radiation damage at studied fluences, and higher energy fast neutron irradiatioin is needed for more conclusive results. Another contribution to this research is a data-driven method employing an effective field theory approach, with the addition of two real scalars, H and X, in troduced and added to SM particles to study the associated Higgs boson production with top quarks at the Large Hadron Collider, at a centre of mass energy of Js = 8 TeV. A benchmark scenario, where the parameters of the model are constrained for mH = 275 GeV and mx = 60 GeV, is considered. From this, a comparative study was performed for the production of the Higgs boson, in association with a single top and top-pairs in the standard model, regarding the processes with h being replaced by the heavy scalar H, further decaying through the channel H ➔ h XX . This study is performed for a single lepton channel first, and then for same-sign leptons, electrons or muons in dilepton events. Different observables, such as b- and c-tagged jet multiplicities, total missing energy, and total scalar sum of transverse momenta of all jets and leptons, are presented. Considering the introduced scalars H and X, an analysis for new physics searches Ill in the Z h channel with missing energy final states at the LHC. The analysis in volves the consideration of a CP-odd, gluon-fusion-produced scalar A decaying into a heavy CP-evcn neutral scalar H with Z boson as A ➔ ZH. H further decays into the CP-even SM Higgs boson h in association with dark matter candidate x - a source of missing energy. The signal final state products are described by Z ➔ z+z- (where z± = e±, µ±) and h ➔ bb decay modes is presented. The masses of the par ticles presented are considered as mh = 125 GeV, mx = 60 GcV, 2mh < mH and mA > mH. Background, from quantum chromodynamic events, is suppressed by imposing selections on the observables. The decreased event numbers for single top, diboson, top pair, W + jets and Z + jets are then compared for same-flavour and for different-flavour decay schemes. This comparison is plotted as a ratio between the two decay schemes.
A dissertation presented in fulfillment of the requirements for the degree of Master of Science (Physics) to the Faculty of Science, University of the Witwatersrand, 2018